IN SILICO ANALYSIS TO CHARACTERISE THE RICE CHITINASE 1 (Oschib1) GENE INDUCED DURING SHEATH BLIGHT INFECTION - DURGA RANI. CH.V, PRAKASAM. V; CHANDRA MOHAN.Y, NARESH BABU PRATHI1, SATENDRA KUMAR MANGRAUTHIA (The Journal of Research, PJTSAU, 2023)
Chitinase enzyme catalyzes the hydrolysis of chitin a-1,4 linkages. Plant chitinases are pathogenesis-related proteins induced in response to pathogen attack and play a critical role in defense against pathogens. Transcriptomic analysis was done to identify the host pathogen interaction in rice to identify many candidate genes inaddition to class III chitinase 1. Class III chitinase 1 (Oschbi1) was identified through transcriptomic data and real time PCR. In this in silico characterization study, we investigated the class III chitinaseI- Oschib1 (Os10g0416500) gene in rice. The databases like RAP-DB, NCBI, RGAP were used for the retrieval of locus information, the nucleotide and amino acid sequences of gene. Using the Pfam database, the chitinase 1 (Oschib1) motifs were identified as glycoside hydrolase-GHL18 and GHL10 family members. Based on the expression and coexpression analysis of rice chitinase gene, plants cannot produce chitin, suggesting that plant chitinases are induced only under biotic or abiotic stress which was not produced under normal condition. Some disease resistance proteins CRKs, AdZADH2 and PBZ1 are co-expressed with chitinase (Oschib1) indicating that the disease resistance genes may have connectivity and are coinducible. NCBI-Blast and NCBI- multiple sequence alignment viewer provided the distance tree results and homology of nucleotides in different cultivars of rice. Interestingly, two more genes belonging to class III chitinase of GHL18 family (Os10g0416100, Os10g0416800) showed high amino acid similarity. Furthermore, major analysis will be done through transgenic approach to characterize the Oschib1 by overexpression of the gene.